A dissolvable hierarchical layered double hydroxide templated from porous zeolitic imidazolate framework-67 for dispersive solid phase extraction of bisphenol A. Issue 32 (31st July 2019) - Ghani, Milad
Abstract : This is the first time that the in situ preparation of advanced extraction media based on a hierarchical layered double hydroxide (HLDH). Abstract : This is the first time that the in situ preparation of advanced extraction media based on a hierarchical layered double hydroxide (HLDH) has been reported in a study. The sorbent was obtained through surfactant-assisted self-assembly of Co(ii )/imidazolate (ZIF-67), followed by in situ conversion of the ZIF-67 into the final HLDH sorbent. The obtained Ni–Co LDH was used for dispersive solid-phase extraction (DSPE) of bisphenol A (BPA) as a model compound from different water samples and a PC baby bottle sample. After the extraction process, elution was accomplished by dissolving the HLDH containing the extracted analytes by changing the solution pH. The applied method didn't use any organic solvents for the extraction and desorption steps and eliminated the problems related to the memory effect of the sorbent in the DSPE method. The extracted analyte was then quantified using high-performance liquid chromatography (HPLC). An optimization strategy based on response surface methodology (RSM) was combined with chromatography analysis. Plackett–Burman design was utilized to screen the experimental factors. The effective factors were then optimized using Central Composite Design (CCD). Under optimum conditions, the linearity range of the method was 0.5–200 μg L −1 . Relative standard deviations (RSDs) were between 4.3% and 5.2%, respectively. The limit of detection (LOD) and limit of quantification (LOQ) were 0.12 μg L −1 and 0.4 μg L −1, respectively. Relative recoveries higher than 92% were achieved in analysis of different environmental water samples.